Direct Water Heater Power Control For Reduced Harmonics And Flicker Content With Optimized Half-cycle Power Control - Komatsu, Wilson; de Oliveira Júnior, Cláudio José; Carvalho, Paulo Sérgio Valle (Eletrônica de Potência, 2006)
This paper presents an optimized Half-Cycle Power Control for Direct Water Heater with reduced harmonic content and flicker control. The method is presented, as well as results of theoretical analysis supported by experimental results.